Examining equity-related eligibility criteria in clinical trials supporting 2022 US drug approvals. - Kathy Sliwinski; Jennifer E Miller; Holly Fernandez Lynch (PLoS ONE)
There has been substantial recent attention to the importance of diversity in clinical trials supporting US Food and Drug Administration (FDA) drug approvals, including both Congressional action and FDA guidance. One factor that can contribute to a lack of diverse enrollment is overly strict eligibility criteria not supported by scientific or safety considerations. The aim of this study was to examine equity-related eligibility criteria in pivotal trials supporting all new molecular entities and therapeutic biologics approved by FDA's Center for Drug Evaluation and Research in 2022. We qualitatively coded these criteria, using a codebook developed through inductive and deductive methods. The codebook consisted of categories relevant to equitable inclusion across race, ethnicity, socioeconomic status, pregnancy, disability, and age; explanations of the potential relevance to equity, as well as potential scientific and regulatory justifications. We found that adolescents, pregnant/lactating individuals, and individuals with limited literacy were most commonly excluded and that about 1 trial in 5 excluded individuals based on weight/obesity, had general exclusions for hepatitis, or excluded adults aged 80 and up. Ultimately, our results indicate that several common eligibility criteria are likely to negatively influence equitable inclusion, especially based on age, pregnancy/lactation, and characteristics associated with race, ethnicity, and socioeconomic status. To minimize unnecessary equity-related exclusions, eligibility should focus on specific issues expected to influence safety or efficacy (e.g., liver function, drug interaction, uncontrolled comorbid disease), rather than blanket exclusion based on broad diagnoses or characteristics. Investigators, sponsors, institutional review boards, and regulators should scrutinize eligibility criteria with equity in mind.